The Sensitivity of Moss-Associated Nitrogen Fixation towards Repeated Nitrogen Input. - Kathrin Rousk (PLoS ONE, 2016)
Nitrogen (N2) fixation is a major source of available N in ecosystems that receive low amounts of atmospheric N deposition. In boreal forest and subarctic tundra, the feather moss Hylocomium splendens is colonized by N2 fixing cyanobacteria that could contribute fundamentally to increase the N pool in these ecosystems. However, N2 fixation in mosses is inhibited by N input. Although this has been shown previously, the ability of N2 fixation to grow less sensitive towards repeated, increased N inputs remains unknown. Here, we tested if N2 fixation in H. splendens can recover from increased N input depending on the N load (0, 5, 20, 80, 320 kg N ha(-1) yr(-1)) after a period of N deprivation, and if sensitivity towards increased N input can decrease after repeated N additions. Nitrogen fixation in the moss was inhibited by the highest N addition, but was promoted by adding 5 kg N ha(-1) yr(-1), and increased in all treatments during a short period of N deprivation. The sensitivity of N2 fixation towards repeated N additions seem to decrease in the 20 and 80 kg N additions, but increased in the highest N addition (320 kg N ha(-1) yr(-1)). Recovery of N in leachate samples increased with increasing N loads, suggesting low retention capabilities of mosses if N input is above 5 kg N ha(-1) yr(-1). Our results demonstrate that the sensitivity towards repeated N additions is likely to decrease if N input does not exceed a certain threshold.